El mototaxismo como medio de transporte y alternativa económica - Belén Torcoroma Quintero Bayona; Blanca Mery Velasco Burgos; Carlos Alberto Pacheco Sánchez (Mundo Fesc)
The use of motorcycle taxis in Colombia as a means of transportation has grown rapidly in recent years, generating a significant impact on public transportation services and becoming an important source of income for those who practice this occupation. The objective of the study was to identify the factors that influence the motorcycle taxi phenomenon in the municipality of Ocaña, Norte de Santander, based on the theory of labor market segmentation, considering concepts such as wage inequality and unemployment. Methodologically, the research was conducted using a quantitative method, with a field survey design administered to 357 people who work in this sector. The most significant finding of the study was that the absence of a boss, lack of work schedules, and lack of daily income for subsistence were the motivating factors that lead the population to choose this activity.